2012
DOI: 10.1007/s12160-012-9377-2
|View full text |Cite
|
Sign up to set email alerts
|

A Psychoeducational Intervention (SWEEP) for Depressed Women with Diabetes

Abstract: Background Clinically significant depression is present in 25 % of individuals with type 2 diabetes, its risk being doubled in women. Purpose To examine the effectiveness of the Study of Women's Emotions and Evaluation of a Psychoeducational (SWEEP), a group therapy for depression treatment based on cognitive behavioral therapy principles that was developed for women with type 2 diabetes was conducted. Methods Women with significantly elevated depression symptoms (Center for Epidemiologic Studies Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(111 citation statements)
references
References 93 publications
3
106
0
2
Order By: Relevance
“…It is clinically relevant to observe that both MBCT and CBT significantly increase well-being and reduce anxiety and diabetes-related distress. These findings are consistent with previous research showing that psychological interventions focusing on depressive symptoms can also improve anxiety and quality of life (10,20). Results are also in line with previous studies in patients with diabetes investigating either MBCT or CBT, also showing reductions in diabetes-related distress (14,19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is clinically relevant to observe that both MBCT and CBT significantly increase well-being and reduce anxiety and diabetes-related distress. These findings are consistent with previous research showing that psychological interventions focusing on depressive symptoms can also improve anxiety and quality of life (10,20). Results are also in line with previous studies in patients with diabetes investigating either MBCT or CBT, also showing reductions in diabetes-related distress (14,19).…”
Section: Discussionsupporting
confidence: 92%
“…CBT has been related to significant improvements in psychological symptoms in patients with a diversity of somatic diseases, especially when delivered individually (18). Regarding CBT in patients with diabetes and comorbid depression, five RCTs have investigated and demonstrated its efficacy (19)(20)(21)(22)(23). Thus, CBT is characterized as the gold standard against which to assess the efficacy of a relatively new and promising intervention like MBCT.…”
mentioning
confidence: 99%
“…Mental health resources are grossly inadequate globally and there is a stark gap between service users and service providers (Saraceno & Saxena, 2002;WHO, 2013c). The success of nurses administering the interventions was reported in the various included studies (Penckofer et al, 2012;Piette et al, 2011;Rungreangkulkij et al, 2011). In psychosocial interventions, the therapeutic alliance that a therapist has with the individual is one of the pivotal factors in Page 26 of 53 A c c e p t e d M a n u s c r i p t 26 determining a successful treatment (Feller & Cottone., 2003).…”
Section: Page 25 Of 53mentioning
confidence: 99%
“…There were also predominantly more female than male participants in this review despite diabetes having similar prevalence rates in men and women (IDF, 2013a), and one study (Penckofer et al, 2012) focused its intervention solely on women. Research has shown that women were more likely to seek help and get diagnosed for their depression than men (Branney & White, 2008;Ogrodniczuk & Oliffe, 2010).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation